Challenges of dairy cooperatives in the area of sales marketing - Konieczna, Izabela (Contemporary organisation and management. Challenges and trends, 2020)
The article sets itself the goal of presenting how cooperatives assess the importance of features of the offer in the area of sales marketing for various groups of customers. The implementation of the goal was based on the presentation and analysis of the results of research conducted among the management of cooperatives from two provinces: Świętokrzyskie and Małopolskie using an interview questionnaire. Research results show that cooperatives from both provinces assessed the importance of features of the offer differently, but their opinions are similar in terms of the group of customers for which the importance of the features of the offer in the area of sales marketing was rated the highest.